Factors Affecting Adoption of Social Media Marketing by Construction MSMEs in Zimbabwe: Case of CIFOZ and SMEA Members in Harare - Chigombe, Patricia; Chundu, Moses; Mucheri, Tolbert (Advances in Social Sciences Research Journal, 2022)
Adoption and usage of social media marketing by MSMEs is critical given the current global trends. The study examined the factors influencing social media adoption by Construction MSMEs in Harare guided by Technology Acceptance Model (TAM), and Chaffey’s theory. A sample of 119 was drawn from CIFOZ and SMEA using systematic and purposive sampling techniques. Questionnaires and interviews were used in data collection and were analysed using SPSS version 25.0, thematic analysis and Nvivo. Positive factors noted were environmental, (at α=0.05 level of significance,) organisational (statistically significant at p-value<0.000) and CEO characteristics towards the adoption of social media marketing by these notwithstanding numerous barriers. The study concludes that while MSMEs in the construction sector appreciate social media marketing and positive factors towards its adoption, there are significant barriers towards its adoption that include lack of expertise, information, high maintenance costs and legal issues. Further, in considering positive factors towards adoption, it is reasonable to conclude that the MSMEs should take account of factors such as managerial and organizational attributes as they have the most significant influence. The study recommended training and establishment of a strategy driven approach by MSMEs in their quest to adopt social media marketing. Findings from this study will guide forward looking policies to ensure no sector is left behind towards a digital economy.